2009
DOI: 10.1111/j.1574-6941.2009.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity of boron-rich volcanic hot springs of  St. Lucia, Lesser Antilles

Abstract: The volcanic Sulphur Springs, St. Lucia, present an extreme environment due to high temperatures, low pH values, and high concentrations of sulfate and boron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…The Shannon-Weaver index [29], H ′ = −Σ( pi )(ln⁡ pi ), and Simpson's reciprocal index [30], 1/ D , where D = Σ( pi ) 2 , and pi is the proportion of phylotypes i relative to the total number of phylotypes, both take richness and evenness into account [13, 28]. The Shannon-Weaver index and Simpson's reciprocal index were calculated using ESTIMATES 8.0 [31].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Shannon-Weaver index [29], H ′ = −Σ( pi )(ln⁡ pi ), and Simpson's reciprocal index [30], 1/ D , where D = Σ( pi ) 2 , and pi is the proportion of phylotypes i relative to the total number of phylotypes, both take richness and evenness into account [13, 28]. The Shannon-Weaver index and Simpson's reciprocal index were calculated using ESTIMATES 8.0 [31].…”
Section: Methodsmentioning
confidence: 99%
“…Hot spring microbial communities have been extensively studied in many areas such as Yellowstone National Park in the United States [510], Kamchatka hot springs in Russia [11], the island of the Lesser Antilles [12, 13], Icelandic hot springs [11, 14], Mt. Unzen hot springs in Japan [15], Ohwakudani hot springs in Japan [16], Pisciarelli hot springs in Italy [17], Bor Khlueng hot springs in Thailand [18], Wai-o-tapu geothermal area in New Zealand [19], and Tengchong hot springs in China [20].…”
Section: Introductionmentioning
confidence: 99%
“…Microbial biography studies in hot springs, a great number carried out in Yellowstone National Park, have shown these environments containing highly distinct community structures, where archaea, cyanobacteria, chloroflexi and acidobacteria are among the microorganisms most commonly found [35,40,[50][51]23,56]. Such studies have typically focused on the broader microbial community and very little is known on the biogeography of actinobacteria in hot springs.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic classification of Attri hot sulfur spring microbiomes showed that the microbial communities were dominated by bacterial domains that was quite similar to the diversity reported in other sulfur thermal springs (Skirnisdottir et al 2000;Stout et al 2009). The bacterial communities found in the sediment sample of Attri Fig.…”
Section: Discussionmentioning
confidence: 80%
“…Comparatively lesser diversification was observed in the communities of Attri hot spring consisting of archaea and eukaryota. Archaea may use more energy in maintaining metabolism in extreme environments and are thus less able to diversify (Stout et al 2009), while the growth of eukaryotic species was probably limited due to elevated temperature.…”
Section: Discussionmentioning
confidence: 99%